Defining educational success through the eyes of young people who have been in foster care : a qualitative case study : a thesis presented in partial fulfilment of the requirements for the degree of Master of Educational Psychology at Massey University, Albany, New Zealand - Miller, Hannah (Massey University, 2019)
All children have the right to an education and a voice, as protected by the United Nations Convention on the Rights of the Child 1989, ratified by New Zealand in 1993. Children and young people in foster care face unique and often challenging experiences that can make them vulnerable to having these basic rights eroded. This study explored how educational success was determined by young people who were in, or had been in, foster care. Specifically, this research addressed how success in educational experiences is identified and enacted by foster care experienced young people, and in what ways formal and informal educational experiences are perceived by, and impact on, these young people’s lives. In-depth semi-structured interviews were conducted with seven participants, aged between 16 and 29 years old, who had experienced foster care and compulsory education in New Zealand. Interviews were analysed using grounded theory. The findings showed that educational successes as identified by young people in this study were broad and holistic. They navigated complex obstacles posed by living in foster care and these impacted on learning and interactions within school. Specific experiences of success differed between participants, and ranged from social acceptance and a sense of belonging, varying degrees of achievement at school, to simply turning up to school. Young people demonstrated marked resilience throughout the challenges they faced, which was both supportive to success, and a success in itself. Relationships with teachers, foster carers and friends were key supports to success, along with having a voice, influence over decisions and having an advocate. The implications of this study include a broadening of the concept of educational success—a concept that takes on different meanings according to people’s values and life experiences. Given the unique life experiences of children and young people in foster care, there is imperative to create space for the voices of children and young people in foster care to both determine and define what educational success means, and they need their rights to share these perspectives to enhance their own educational experiences.
Keywords: Foster children; Education; New Zealand; Ex-foster children; Attitudes; 520102 Educational psychology